2014
DOI: 10.1002/dta.1736
|View full text |Cite
|
Sign up to set email alerts
|

Possible cause of lack of positive samples on homologous blood transfusion

Abstract: Homologous blood transfusion is a prohibited method of blood manipulation that can be used to increase the number of erythrocytes circulating in the blood stream resulting in an increased oxygen transport capacity. In doping controls, homologous blood transfusions are determined by means of a procedure based on the detection of red blood cell phenotypes by flow cytometry. In the past six years, no adverse analytical findings concerning homologous blood transfusions were reported. One explanation for that pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 11 publications
2
12
0
5
Order By: Relevance
“…Не затрагивая достаточно короткий текст самой публикации [35], уже сам абстракт публикации заставляет насторожиться читателя, не готового к столь неуместной манипуляции сознанием: здесь и подмена понятий, и нарушения логики, и очевидная презумпция виновности российских спортсменов, и пренебрежение фундаментальными основами математической статистики и др.…”
Section: русская народная поговоркаunclassified
See 1 more Smart Citation
“…Не затрагивая достаточно короткий текст самой публикации [35], уже сам абстракт публикации заставляет насторожиться читателя, не готового к столь неуместной манипуляции сознанием: здесь и подмена понятий, и нарушения логики, и очевидная презумпция виновности российских спортсменов, и пренебрежение фундаментальными основами математической статистики и др.…”
Section: русская народная поговоркаunclassified
“…Абстракт текста [35] начинается с утверждения, что «гомологическое переливание крови -это запрещённый метод манипуляций с кровью». Однако гомологическое переливание крови (профессионалы, вообще-то, говорят, «инфузионно-трансфузионная терапия») -этот общепринятый метод лечения!…”
Section: русская народная поговоркаunclassified
“…Additional studies have, however, been suggested to account for factors potentially compromising the approach, especially the to‐date permitted supplementation of iron . Further to these considerations, the prevalence of team mates sharing the same RhD factor and AB0 blood group raised suspicion as to whether carefully selected blood donors (with matching erythrocyte surface antigens) are accompanying cheating athletes as team members . This strategy would de facto undermine testing approaches based on monitoring ex vivo storage‐induced parameters (e.g.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…[234] Further to these considerations, the prevalence of team mates sharing the same RhD factor and AB0 blood group raised suspicion as to whether carefully selected blood donors (with matching erythrocyte surface antigens) are accompanying cheating athletes as team members. [235] This strategy would de facto undermine testing approaches based on monitoring ex vivo storage-induced parameters (e.g. plasticizers, iron) and most likely common analytical assays for the detection of homologous blood transfusion but presumably not the ABP.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…Blood doping remains a major analytical challenge. Further progress in the field of homogenous as well as autologous transfusion is presented . Improvements in fast detection of doping with recombinant erythropoietin using MAIIA technology might still prove useful in the future …”
mentioning
confidence: 99%